On the wrong track: Sustainable and low-emission blue food diets to mitigate climate change - Atalah, Javier; Sanchez-Jerez, Pablo (Frontiers in Sustainable Food Systems, 2022)
Seafood and other aquatic food (blue food) are often advocated as sustainable protein sources crucial to meeting global food demand. Consumption choices allow citizens to take actions that reduce the environmental burden of food production and tackle the climate crisis. Here we used a high-resolution Spanish national-level dataset collected from 12,500 households between 1999 and 2021 as a study case to assess trends in blue food consumption concerning sources, types and stressors resulting from their production. By aggregating species groups according to source, we found an overall reduction in the consumption of most wild species. For farmed species, we found a pronounced increase in the consumption of carnivorous fish and an overall decrease in low trophic-level species consumption, such as bivalves. Using published studies, we estimated greenhouse gases, nitrogen, and phosphorus emissions to assess trends in environmental footprint. Low performance was associated with the consumption of high trophic-level species intensively farmed in distant regions, such as carnivorous fish, due to high stressor emissions related to their production and transport. Across all groups, consumption of locally farmed bivalves conduced to the lowest stressor emissions, providing an example of ‘net-zero’ blue food. Our analysis identified historical trends in the environmental footprint of blue food consumption and consumers’ choices that promote environmentally sustainable diets. It also highlights vast differences in the ecological footprint associated with the consumption of aquaculture-sourced protein. Based on our assessment, we recommend refocusing consumption patterns towards farmed species with small environmental footprints, such as locally produced low trophic-level species, and implementing policies that increase consumers’ environmental awareness and minimise food production systems’ footprints. Considering global blue food demand is predicted to nearly double by mid-century, consumers’ choices can significantly impact sustainable production practices and mitigate climate change.